Fabrication and in vitro evaluation of diclofenac sodium microparticles. Issue 3 (19th December 2016) - Zaman, Muhammad; Batool, Nighat; Atta-Ur-Rehman,
Abstract : The present study was designed with the aim to succeed in formulating a microparticulate drug delivery system of diclofenac sodium by using ethyl cellulose and Eudragit L100. The solvent evaporation technique was used to fabricate five different types of formulations by varying the concentrations of the polymers as well as the drug-to-polymer ratios. The prepared microparticles were subjected to micromeritics, chemical compatibility between drug and polymers, surface morphology, in vitro dissolution studies and kinetic modelling of release data. The results revealed that the microparticles were free-flowing and chemically compatible. The microparticles were spherical to irregularly shaped with a rough surface. The drug contents of the particles were quite satisfactory, and the release of the drug was sustained with anomalous case II transport type of release mechanism. The statistical analysis (analysis of variance) advocated the significant impact ( p < 0·05) of variations in the polymer concentration on drug release. Finally, successful preparation of diclofenac sodium was confirmed with a suitable sustained effect.